Proof of Concept of an Eclectic, Integrative Therapeutic Approach to Mental Health and Well-Being Through Virtual Reality Technology - Frewen, Paul; Mistry, Divya; Zhu, Jenney; Kielt, Talia; Wekerle, Christine; Lanius, Ruth A.; Jetly, Rakesh (Frontiers in Psychology, 2020)
Across three studies we provide a proof of concept evaluation of an integrative psychotherapeutic application of virtual reality (VR) technology. Study 1 (n = 36) evaluated an unguided “safe-place” imagery task, where participants were instructed “to create a safe space… [such as] a scene, item, design, or any visual representation that makes you feel safe” using either the Google Tilt Brush application (VR condition), the standard Microsoft Paint application (2-D condition), or via eyes-closed mental imagery alone (IMG condition). Study 2 (n = 48) evaluated a narrative episodic recall task, where participants viewed their childhood and adult homes and places of schooling either using either the Google Earth VR application (VR condition), the standard Google Earth application (2-D condition), or recalled these places with their eyes closed via mental imagery alone (IMG condition). Finally, study 3 (n = 48) evaluated a guided wilderness imagery task, during which different scripts were narrated, specifically, a trail walk in autumn, a spring meadow, and a hillside walk in snowy winter, while either these same scenes were visually presented using the Nature Treks VR application (VR condition), the scenes were presented using the same software but shown on standard computer monitor (2-D condition), or participants’ eyes were closed (IMG condition). Order of intervention format was randomized across participants. Across all three studies, quantitative survey ratings showed that the VR format of intervention delivery produced greater positive affect and satisfaction and perceived credibility ratings as an intervention for trauma- and stressor-related disorders and psychological wellbeing as rated by university students who varied in traumatic and stressful life event history and symptoms of posttraumatic stress disorder (PTSD), while qualitative findings revealed additional themes of experiential response including increased experience of presence and vividness in the VR condition. Future research directions and clinical applications are discussed.